2012
DOI: 10.1002/hc.21055
|View full text |Cite
|
Sign up to set email alerts
|

C–N Coupling of 1,2‐Dihydro‐2,2,4‐trimethylquinoline Derivatives via a Silver(I)‐Catalyzed Direct Functionalization of a C–H Bond

Abstract: Two C,N‐linked dimeric 1,2‐dihydro‐2,2,4‐trimethylquinolines, namely 6‐chloro‐1‐(6‐chloro‐1,2‐dihydro‐2,2,4‐trimethylquinolin‐8‐yl)‐1,2‐dihydro‐2,2,4‐trimethylquinoline (3a) and 6‐ethoxy‐1‐(6‐ethoxy‐1,2‐dihydro‐2,2,4‐trimethylquinolin‐8‐yl)‐1,2‐dihydro‐2,2,4‐trimethylquinoline (3b), have been prepared through a silver‐catalyzed dimerization of their corresponding monomers. The effect of different silver salts on the reaction was also investigated, and the obtained results suggest that silver ions effectively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Fotie and co-workers reported a C-N coupling of 1,2-dihydro-2,2,4-trimethylquinoline derivatives 45 via a silver(I)-catalyzed Csp 2 -H functionalization (Scheme 25). 28 This represents one of the rare reports on the silver-catalyzed C-N bond formation through the coupling of a secondary amine and an activated aromatic system via a direct C-H functionalization.…”
Section: Silver-catalyzed C-h Bond Functionalizationmentioning
confidence: 95%
“…Fotie and co-workers reported a C-N coupling of 1,2-dihydro-2,2,4-trimethylquinoline derivatives 45 via a silver(I)-catalyzed Csp 2 -H functionalization (Scheme 25). 28 This represents one of the rare reports on the silver-catalyzed C-N bond formation through the coupling of a secondary amine and an activated aromatic system via a direct C-H functionalization.…”
Section: Silver-catalyzed C-h Bond Functionalizationmentioning
confidence: 95%
“…C–N linked biphenyls were prepared by dimerizing the corresponding aniline derivative via a silver(I) catalyzed direct C–H functionalization, as illustrated in Scheme 5. 46 As for 2’-aminobiphenyl-2-ols, the largest family of compounds screened during this study, they were also prepared using silver(I) as a catalyst under reaction conditions very similar to those used in the preparation of C–N linked biphenyls. In this latter case, the aniline derivative was cross-coupled with the appropriate phenol via a regioselective aerobic oxidative cross-coupling, resulting also in a direct C–H functionalization.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we reported that silver(I) could effectively catalyzed the C-H/N-H direct homocoupling of secondary arylamines resulting in the formation of a new intermolecular C-N bond. 11 In a process of expanding the scope of this reaction to include cross-couplings, we noticed that N,N,4-trimethylaniline reacts with 2-naphthol in the presence of Na 2 S 2 O 8 (1 eqv) and AgNO 3 (10% mol) resulting in a regioselective formation of a carbon-carbon bond at the ortho position to the hydroxyl and amine functional groups in the respective substrates, with a very low yield (Table 1, enty1). Based on this initial observation, we decided to use both substrates for a further optimization of the reaction conditions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the difference in oxidation potentials (naphthol = 1.87 eV, phenol = 2.10 eV), 8b, 10 all these reactions failed when any phenol derivative other than naphthols was used as a coupling partner. 9 As part of our continuous effort to investigate the effect of silver(I) in the oxidative dehydrogenative coupling of arenes resulting in the formation of C-N bonds, 11 we noticed that silver(I) can mediate the regioselective cross-coupling of phenol and aniline derivatives resulting in the exclusive formation of 2'-aminobiphenyl-2-ol derivatives, under very mild conditions. To the best of our knowledge, this is not only the first report that combines silver(I) and H 2 O 2 to achieve this type of conversion, but it is also one of the rare cases where the scope of the reaction is expanded to include a wide range of phenol derivatives other than 2-naphthol and 1-naphthol.…”
Section: Introductionmentioning
confidence: 99%